The use of bay leaf (Eugenia polyantha Wight) in dentistry - Agus Sumono; Agustin Wulan SD (Dental Journal (Majalah Kedokteran Gigi), 2008)
Background: Bay leaf or Eugenia polyantha Wight is a species that has several chemical properties. Bay leaf consists of tanine, flavonoid, essensial oil, including citric acid and eugenol. However, only few reports were published about the use of bay leaf in dentistry. Purpose: The aim of this article is to describe the chemical properties of Eugenia polyantha Wight that are widely used in dentistry. Reviews: The chemical properties of Eugenia polyantha Wight have analgesic, antibacterial, and anti-inflammatory effect, so they can be used as an alternative dental therapy. These properties can be used as a basic of therapy or as a basic ingredients of treatment. Conclusion: Eugenia polyantha Wight has some useful pharmacologic activities that are useful in dentistry. We suggest this article can be used as a basic knowledge for dental researchers.